2021
DOI: 10.1007/s40618-021-01682-6
|View full text |Cite
|
Sign up to set email alerts
|

Higher testosterone is associated with increased inflammatory markers in women with SARS-CoV-2 pneumonia: preliminary results from an observational study

Abstract: Purpose Objective of this study was to assess the association between testosterone (T) levels and biochemical markers in a cohort of female patients admitted for SARS-CoV-2 infection in a respiratory intensive care unit (RICU). Methods A consecutive series of 17 women affected by SARSCoV-2 pneumonia and recovered in the RICU of the Hospital of Mantua were analyzed. Biochemical inflammatory markers as well as total testosterone (TT), calculated free T (cFT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
3
6
0
Order By: Relevance
“…A study by stasi et al has assessed the role of testosterone in a cohort of women with sARs-COV-2 pneumonias. The result showed that the higher total testosterone and calculated free testosterone are associated with a greater severity of the disease [149].…”
Section: Covid-19 In Patients With Androgenic Alopeciamentioning
confidence: 93%
“…A study by stasi et al has assessed the role of testosterone in a cohort of women with sARs-COV-2 pneumonias. The result showed that the higher total testosterone and calculated free testosterone are associated with a greater severity of the disease [149].…”
Section: Covid-19 In Patients With Androgenic Alopeciamentioning
confidence: 93%
“…Contrary to the effect seen in men, one small study reports that higher T levels in women with COVID-19 pneumonia have been reported to be correlated with a more robust inflammatory response. 25 …”
Section: Factors Accounting For Trend Of Male Predominant Severe Covi...mentioning
confidence: 99%
“…[24,25]. Other data particularly concerning COVID-19 infection, showed, for instance, as cortisol associates with inflammation markers, so is total testosterone and calculated free testosterone in females with pneumonia due to more intense adrenal cortex activity [26]. Particular aspects related to coronavirus infectionassociated stress include anomalies of coagulation profile in addition to platelets damage as reflected by increased D-dimers, fibrinogen, and coagulation factor VIII, as well as low anticoagulant protein S and activated protein C, reduced coagulation factor XII [27].…”
Section: Cortisol As Stress Hormonementioning
confidence: 98%